MXene-based electrode material based on hydrazine hydrate gas expansion assisted pore forming and preparation method and application thereof
By using hydrazine hydrate gas expansion-assisted pore-forming method, the self-stacking problem of MXene materials under high load was solved, the specific surface area and porosity of MXene-based electrodes were improved, the electrochemical performance was enhanced, and high capacity and stable electrochemical performance under high load were achieved.
Patent Information
- Application Number
- CN202411728715.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-07
AI Technical Summary
MXene materials are prone to self-stacking under high load conditions, which leads to the collapse of the pore structure, restricts the diffusion of electrolyte ions, reduces the specific surface area and conductivity, and affects the electrochemical performance and the energy density and power density of supercapacitors.
The method of hydrazine hydrate gas expansion-assisted pore formation involves mixing MXene-OH with bacterial cellulose and then vacuum drying it. The hydrazine hydrate solution is then decomposed under vacuum heating to generate gas, which disrupts the stacking force of MXene sheets, forming a large number of pore structures and introducing oxygen-containing functional groups and amino groups to regulate surface chemical properties.
It significantly improves the specific surface area and porosity of MXene-based electrode materials, promotes electrolyte ion insertion and extraction, enhances power density and cycle stability, maintains high capacity under high load, and achieves a specific capacitance of up to 625 F g⁻¹.
Smart Images

Figure CN119274993A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, and a preparation method and application thereof. Background Art
[0002] MXene two-dimensional materials have become a research hotspot for supercapacitor electrode materials due to their excellent conductivity, large specific surface area and good electrochemical properties. Although MXene materials have significant electrochemical properties, they still face the following challenges in practical applications: the layered structure of MXene materials has a strong stacking tendency, especially under high load conditions, the interlayer force of MXene is strong, and self-stacking occurs easily, resulting in the collapse of the pore structure of the material, which in turn limits the effective diffusion and storage of electrolyte ions. The stacking of the layered structure not only reduces the specific surface area of the electrode, but also causes the discontinuity of the conductive network, seriously affecting the conductivity and cycle stability of the electrode. Although MXene materials have a high theoretical capacity, their electrochemical properties often cannot maintain an ideal state under high load conditions. The stacking phenomenon of the layered structure not only affects the capacitance of MXene materials under high load conditions, but also affects the overall energy density and power density of supercapacitors. Therefore, how to inhibit the stacking behavior of MXene and enhance its electrochemical performance under high load has become a technical difficulty that needs to be urgently solved in the industrialization of MXene electrodes. Summary of the invention
[0003] In response to the technical problems existing in the prior art, the present invention provides a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation and a preparation method and application thereof, so as to suppress the stacking behavior of MXene and enhance its electrochemical performance under high load.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising: The MXene-OH mixed solution is mixed with the bacterial cellulose dispersion, and then vacuum filtered and dried at a constant temperature in a vacuum to obtain a MXene-OH / BC film; Laying a MXene-OH / BC film on the upper surface of a first ceramic sheet to which a hydrazine hydrate solution has been dropped, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, laying a second ceramic sheet on the upper surface of the MXene-OH / BC film, to obtain an intermediate with a sandwich structure; The intermediate with the sandwich structure is vacuum heated to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0005] Furthermore, when the MXene-OH mixed solution is mixed with the bacterial cellulose dispersion, the mass ratio of the MXene-OH mixed solution to the bacterial cellulose dispersion is 4:1-3:2; wherein the concentration of the MXene-OH mixed solution is 3-5 mg / mL, and the concentration of the bacterial cellulose dispersion is 3-5 mg / mL.
[0006] Furthermore, during vacuum constant temperature drying, the drying temperature is 95-105° C. and the drying time is 5-10 min.
[0007] Furthermore, the hydrazine hydrate solution adopts 80% hydrazine hydrate.
[0008] Furthermore, the first ceramic sheet and the second ceramic sheet are both made of alumina ceramic sheets.
[0009] Furthermore, when the intermediate with the sandwich structure is heated in vacuum, the heating temperature is 90-95° C. and the heating time is 5-6 hours.
[0010] Furthermore, the MXene-OH mixed solution is made by mixing Ti3C2T x The MXene suspension is mixed with potassium hydroxide and stirred.
[0011] The present invention also provides a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, which is prepared by using the preparation method of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0012] Furthermore, the mass specific capacitance of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation is 368.6-625.63Fg -1 .
[0013] The present invention also provides an application of a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, and the application of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation in a supercapacitor.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation. The MXene in the MXene-OH mixed solution is subjected to the action of KOH, and its sheet layer is wrinkled and deformed, so that the MXene surface obtains more defects and cracks, and a large number of oxygen-containing functional groups are also introduced, providing reaction sites for the subsequent hydrazine hydrate gas expansion; secondly, the hydrazine hydrate solution is decomposed under heating conditions to release a large amount of gas, and the expansion effect of the hydrazine hydrate gas breaks through the stacking force between the MXene sheets, resulting in a large number of pore structures inside the MXene film; the newly formed pores significantly increase the specific surface area and porosity of the MXene, and more pores can promote faster insertion and removal of electrolyte ions. The electrode improves its power density and cycle stability; at the same time, the reaction of hydrazine hydrate with oxygen-containing functional groups on the surface of MXene further regulates the surface chemical properties of MXene; specifically, the reduction reaction of hydrazine hydrate with oxygen-containing functional groups reduces part of the oxidized functional groups on the surface of MXene to functional groups with carbonyl groups; the introduction of amino groups is also in the hydrazine hydrate reaction. The presence of amino groups can not only increase the electron density of MXene, but also enhance its electronic conductivity and promote the rapid transfer of charges, which has an important role in promoting the charge storage and release process in batteries and supercapacitors; the MXene-based electrode material based on hydrazine hydrate gas expansion assisted pore formation prepared by the present invention can still maintain high capacity under high load; among them, at 5mgcm -2 The mass specific capacitance can reach 625Fg under the load -1 , at 10mgcm -2 Under the load of (international standard load), the mass specific capacitance can reach 368Fg -1 , which has practical significance for the industrialization of MXene-based supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is a planar scanning electron microscope image of a MXene-based electrode material prepared in a comparative example based on hydrazine hydrate gas expansion-assisted pore formation; Figure 2 This is a planar scanning electron microscope image of the MXene-based electrode material prepared in Example 1 based on hydrazine hydrate gas expansion-assisted pore formation; Figure 3This is a planar scanning electron micrograph of the MXene-based electrode material prepared in Example 2 based on hydrazine hydrate gas expansion-assisted pore formation; Figure 4 This is a planar scanning electron microscope image of the MXene-based electrode material prepared in Example 3 based on hydrazine hydrate gas expansion-assisted pore formation; Figure 5 This is a planar scanning electron microscope image of the MXene-based electrode material prepared in Example 4 based on hydrazine hydrate gas expansion-assisted pore formation; Figure 6 It is a graph showing the relationship between the mass specific capacitance and the current density of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation prepared in the comparative example and Examples 1-4; Figure 7 This is a graph showing the relationship between the mass specific capacitance and current density of the MXene-based electrode material prepared in Example 5 based on hydrazine hydrate gas expansion-assisted pore formation. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely in combination with the drawings in the embodiments of this application; obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0018] The present invention provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T x MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 5-10 mg / mL.
[0019] Step 2: The Ti3C2T x The MXene suspension and potassium hydroxide are mixed in a mass ratio of 1:(0.5-3), and stirred at 25-35° C. for 8-9 hours to obtain a MXene-OH mixed solution; wherein the stirring speed is 5-10 rpm, and the concentration of the MXene-OH mixed solution is 3 mg / mL.
[0020] Step 3, subjecting the bacterial cellulose (BC) gel block to high-temperature impurity removal at 100-105°C for 1 hour to obtain a bacterial cellulose gel block after impurity removal; adding the bacterial cellulose gel after impurity removal into deionized water, and then shearing it at 1000-1500r / min for 5-10min to obtain a bacterial cellulose dispersion; wherein the concentration of the bacterial cellulose dispersion is 3-5mg / mL.
[0021] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 4:1-3:2, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at a temperature of 95-105°C under vacuum for 5-10 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 105-210 mg, and the loading amount of the active substance is 5-10 mg cm -2 .
[0022] Step 5, drop 180-320 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been dropped, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0023] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish, and heat it in a vacuum oven at 90-95° C. for 5-6 hours to decompose the hydrazine hydrate to produce gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0024] Preparation principle: The preparation method of MXene-based electrode material based on hydrazine hydrate gas expansion assisted pore formation of the present invention comprises the following steps: xThe MXene suspension is mixed with potassium hydroxide and stirred. The MXene sheets are wrinkled and deformed by the action of KOH to obtain more defects and cracks on the MXene surface. At the same time, a large number of oxygen-containing functional groups are introduced to provide reaction sites for the subsequent gas expansion of hydrazine hydrate. Secondly, the hydrazine hydrate solution decomposes and releases a large amount of gas under vacuum heating conditions. The expansion of hydrazine hydrate gas breaks through the stacking force between the MXene sheets, resulting in a large number of pore structures inside the MXene film. The newly formed pores significantly increase the specific surface area and porosity of MXene. More pores can promote electrical The faster embedding and extraction of electrolyte ions from the electrode improves its power density and cycle stability. At the same time, the reaction of hydrazine hydrate with oxygen-containing functional groups on the surface of MXene further regulates the surface chemical properties of MXene. The reduction reaction of hydrazine hydrate with oxygen-containing functional groups reduces part of the oxidized functional groups on the surface of MXene to functional groups with carbonyl groups. In addition, amino groups can be introduced in the hydrazine hydrate reaction. The presence of amino groups can not only increase the electron density of MXene, but also enhance its electronic conductivity and promote the rapid transfer of charge, which plays an important role in promoting the charge storage and release process in batteries and supercapacitors.
[0025] The MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation prepared by the present invention can maintain high capacity under high load; wherein the mass specific capacitance of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation is 368.6-625.63Fg -1 ; Specifically, at 5mgcm -2 The mass specific capacitance can reach 625.63Fg under the load -1 , 10mgcm -2 Under the load of (international standard load), the mass specific capacitance can reach 368.6Fg -1 .
[0026] Comparative Example This comparative example provides a method for preparing a MXene-based electrode material, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T x MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 5 mg / mL.
[0027] Step 2: The bacterial cellulose (BC) gel block is subjected to high-temperature impurity removal at 100° C. for 1 hour to obtain a bacterial cellulose gel block after impurity removal; the bacterial cellulose gel after impurity removal is added into deionized water, and then sheared at 1000 r / min for 5 minutes to obtain a bacterial cellulose dispersion; wherein the concentration of the bacterial cellulose dispersion is 3 mg / mL.
[0028] Step 3: The Ti3C2T x The MXene suspension and the BC dispersion were mixed in a mass ratio of 3:2, and filtered by vacuum assisted filtration to obtain a wet film; the wet film was vacuum dried at 105°C for 10 minutes to obtain a MXene / BC film; wherein the total mass of the MXene and BC mixed was 105 mg, and the loading amount of the active substance was 5 mg cm -2 .
[0029] Step 4, drop 320 μL of hydrazine hydrate solution with a mass fraction of 80% on the first alumina ceramic sheet; lay the MXene / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been dropped, so as to soak the MXene / BC film with the hydrazine hydrate solution; after the MXene / BC film is completely soaked with the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene / BC film to obtain an intermediate with a sandwich structure.
[0030] Step 5: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 90° C. for 5 hours to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material.
[0031] Performance Test: The MXene-based electrode material prepared in the comparative example was tested experimentally. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 297.68 F g -1 The mass specific capacitance.
[0032] Example 1 This embodiment 1 provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T xMXene suspension; wherein the Ti3C2T x The concentration of the MXene suspension was 8 mg / mL.
[0033] Step 2: The Ti3C2T x The MXene suspension was mixed with potassium hydroxide in a mass ratio of 1:0.5 and stirred at 8 rpm for 8 h at 30 °C to obtain a MXene-OH mixed solution with a concentration of 3 mg / mL.
[0034] Step 3, high-temperature decontamination of the bacterial cellulose (BC) gel block at 100° C. for 1 hour to obtain a decontaminated bacterial cellulose gel block; the decontaminated bacterial cellulose gel is added to deionized water, and then sheared at 1500 r / min for 8 minutes to obtain a bacterial cellulose dispersion with a concentration of 4 mg / mL.
[0035] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 4:1, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at 105°C for 10 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 105 mg, and the loading amount of the active substance is 5 mg cm -2 .
[0036] Step 5. Add 180 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been added, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0037] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 95° C. for 6 hours to decompose the hydrazine hydrate to produce gas expansion, thereby obtaining the MXene-based electrode material with hydrazine hydrate gas expansion-assisted pore formation.
[0038] Performance Test: The MXene-based electrode material prepared in Example 1 was tested for hydrazine hydrate gas expansion-assisted pore formation. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 1.34 Å, the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation exhibited a conductivity of 370.74 F g -1 The mass specific capacitance.
[0039] Example 2 This embodiment 2 provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T x MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 10 mg / mL.
[0040] Step 2: The Ti3C2T x The MXene suspension was mixed with potassium hydroxide in a mass ratio of 1:1 and stirred at 10 rpm for 8 h at 35 °C to obtain a MXene-OH mixed solution with a concentration of 4 mg / mL.
[0041] Step 3, the bacterial cellulose (BC) gel block is subjected to high-temperature impurity removal at 100° C. for 1 hour to obtain a bacterial cellulose gel block after impurity removal; the bacterial cellulose gel after impurity removal is added to deionized water, and then sheared at 1000 r / min for 10 minutes to obtain a bacterial cellulose dispersion with a concentration of 5 mg / mL.
[0042] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 3:2, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at 105°C for 8 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 105 mg, and the loading amount of the active substance is 5 mg cm -2 .
[0043] Step 5. Add 320 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been added, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0044] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 90° C. for 5 hours to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0045] Performance Testing: The MXene-based electrode material prepared in Example 2 was tested for hydrazine hydrate gas expansion-assisted pore formation. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 1.37 W / m, the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation exhibited a conductivity of 625.63 F g -1 The mass specific capacitance.
[0046] Example 3 This embodiment 3 provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T x MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 10 mg / mL.
[0047] Step 2: The Ti3C2T x The MXene suspension was mixed with potassium hydroxide in a mass ratio of 1:2 and stirred at 10 rpm for 8 h at 25 °C to obtain a MXene-OH mixed solution with a concentration of 5 mg / mL.
[0048] Step 3, the bacterial cellulose (BC) gel block is subjected to high-temperature impurity removal at 100° C. for 1 hour to obtain a bacterial cellulose gel block after impurity removal; the bacterial cellulose gel after impurity removal is added to deionized water, and then sheared at 1000 r / min for 10 minutes to obtain a bacterial cellulose dispersion with a concentration of 5 mg / mL.
[0049] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 3:2, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at 105°C for 10 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 105 mg, and the loading amount of the active substance is 5 mg cm -2 .
[0050] Step 5. Add 320 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been added, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0051] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 90° C. for 5 hours to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0052] Performance Test: The MXene-based electrode material prepared in Example 3 was tested for hydrazine hydrate gas expansion-assisted pore formation. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 1.37 W / m, the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation exhibited a high conductivity of 605.63 F g -1 The mass specific capacitance.
[0053] Example 4 This embodiment 4 provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2T x MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 10 mg / mL.
[0054] Step 2: The Ti3C2T x The MXene suspension was mixed with potassium hydroxide in a mass ratio of 1:3 and stirred at 10 rpm for 8 h at 25 °C to obtain a MXene-OH mixed solution with a concentration of 3 mg / mL.
[0055] Step 3, the bacterial cellulose (BC) gel block is subjected to high-temperature impurity removal at 100° C. for 1 hour to obtain a bacterial cellulose gel block after impurity removal; the bacterial cellulose gel after impurity removal is added to deionized water, and then sheared at 1000 r / min for 10 minutes to obtain a bacterial cellulose dispersion with a concentration of 5 mg / mL.
[0056] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 3:2, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at 105°C for 10 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 105 mg, and the loading amount of the active substance is 5 mg cm -2 .
[0057] Step 5. Add 320 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been added, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0058] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 90° C. for 5 hours to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0059] Performance Test: The MXene-based electrode material prepared in Example 4 was tested for hydrazine hydrate gas expansion-assisted pore formation. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 5.17 W / m, the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation exhibited a high conductivity of 513.81 F g -1 The mass specific capacitance.
[0060] Example 5 This embodiment 5 provides a method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, comprising the following steps: Step 1: Mix lithium fluoride and hydrochloric acid solution to obtain a fluorine-containing salt solution; add Ti3AlC2MAX to the fluorine-containing salt solution, stir to perform etching reaction, and obtain a mixed solution after reaction; centrifuge, wash, oscillate, and ultrasonically treat the mixed solution after reaction to obtain Ti3C2Tx MXene suspension; wherein the Ti3C2T x The concentration of MXene suspension was 10 mg / mL.
[0061] Step 2: The Ti3C2T x The MXene suspension was mixed with potassium hydroxide in a mass ratio of 1:1 and stirred at 10 rpm for 8 h at 25 °C to obtain a MXene-OH mixed solution with a concentration of 3 mg / mL.
[0062] Step 3, high-temperature decontamination of the bacterial cellulose (BC) gel block at 100° C. for 1 hour to obtain a decontaminated bacterial cellulose gel block; the decontaminated bacterial cellulose gel is added to deionized water, and then sheared at 1200 r / min for 10 minutes to obtain a bacterial cellulose dispersion with a concentration of 5 mg / mL.
[0063] Step 4: Mix the MXene-OH mixed solution and the BC dispersion in a mass ratio of 3:2, and filter by vacuum assisted filtration to obtain a wet film; dry the wet film at 105°C for 10 minutes to obtain a MXene-OH / BC film; wherein the total mass of the mixed MXene-OH and BC is 210 mg, and the loading amount of the active substance is 10 mg cm -2 .
[0064] Step 5. Add 320 μL of 80% hydrazine hydrate on the first alumina ceramic sheet; lay the MXene-OH / BC film on the upper surface of the first alumina ceramic sheet to which the hydrazine hydrate solution has been added, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, lay a second alumina ceramic sheet on the upper surface of the MXene-OH / BC film to obtain an intermediate with a sandwich structure.
[0065] Step 6: Place the intermediate with the sandwich structure as a whole in a culture dish and heat it in a vacuum oven at 90° C. for 5 hours to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
[0066] Performance Testing: The MXene-based electrode material prepared in Example 5 was tested for hydrazine hydrate gas expansion-assisted pore formation. The test results showed that: -2 The loading amount, 1Ag -1 At a current density of 1.37 W / m, the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation exhibited a conductivity of 368.6 F g-1 The mass specific capacitance.
[0067] As attached Figure 1-5 As shown, attached Figure 1 The planar scanning electron micrograph of the MXene-based electrode material prepared in the comparative example based on hydrazine hydrate gas expansion assisted pore formation is given in the attached Figure 2-5 The planar scanning electron micrographs of the MXene-based electrode materials based on hydrazine hydrate gas expansion assisted pore formation prepared in Examples 1-4 are given in the accompanying drawings. Figure 1 It can be seen that the interlayers of the MXene-based electrode material prepared in the comparative example based on hydrazine hydrate gas expansion-assisted pore formation are not completely opened, and there is almost no pore structure; the reason is that: MXene has not been treated with KOH, so that the oxygen-containing functional groups on the MXene surface are relatively few, making it difficult to react with hydrazine hydrate and replace functional groups; from the attached Figure 2-5 It can be seen that the thickness and pore size of the MXene-based electrode materials prepared in Examples 2-5 based on hydrazine hydrate gas expansion-assisted pore formation are significantly enlarged, which helps to improve the wettability of the electrolyte and the ion transfer efficiency, thereby maintaining a higher capacity and better stability under high load.
[0068] As attached Figure 6 As shown, attached Figure 6 The relationship between the mass specific capacitance and the current density of the MXene-based electrode materials based on hydrazine hydrate gas expansion assisted pore formation prepared in the comparative example and Examples 1-4 is given in the figure; Figure 6 It can be seen that with the increase of KOH concentration, the mass specific capacitance of the electrode materials prepared in Examples 1-4 first increases and then decreases, but they are all higher than the mass specific capacitance of the electrode materials prepared in the comparative example; among them, when the MXene suspension and potassium hydroxide are mixed in a mass ratio of 1:1, 1Ag -1 At a current density of 1.37 W, it exhibits the best mass specific capacitance of 625.63 Fg. -1 .
[0069] As attached Figure 7 As shown, attached Figure 7 The relationship between the mass specific capacitance and the current density of the MXene-based electrode material based on hydrazine hydrate gas expansion assisted pore formation prepared in Example 5 is given in the figure; Figure 7 It can be seen that the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation prepared under the condition of a 1:1 mixing ratio of MXene suspension and potassium hydroxide has a high conductivity at 1Ag. -1 At a current density of 10 mg cm -2 Under the high load of international standards, it showed 368.6Fg -1 The mass specific capacitance.
[0070] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.
Claims
1. A method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, characterized in that: include: The MXene-OH mixed solution is mixed with the bacterial cellulose dispersion, and then vacuum filtered and dried at a constant temperature in a vacuum to obtain a MXene-OH / BC film; Laying a MXene-OH / BC film on the upper surface of a first ceramic sheet to which a hydrazine hydrate solution has been dropped, so as to wet the MXene-OH / BC film with the hydrazine hydrate solution; after the MXene-OH / BC film is completely wetted by the hydrazine hydrate solution, laying a second ceramic sheet on the upper surface of the MXene-OH / BC film, to obtain an intermediate with a sandwich structure; The intermediate with the sandwich structure is vacuum heated to decompose the hydrazine hydrate to generate gas expansion, thereby obtaining the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation.
2. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: When the MXene-OH mixed solution is mixed with the bacterial cellulose dispersion, the mass ratio of the MXene-OH mixed solution to the bacterial cellulose dispersion is 4:1-3:2; wherein the concentration of the MXene-OH mixed solution is 3-5 mg / mL, and the concentration of the bacterial cellulose dispersion is 3-5 mg / mL.
3. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: During vacuum constant temperature drying, the drying temperature is 95-105°C and the drying time is 5-10min.
4. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: The hydrazine hydrate solution adopts 80% hydrazine hydrate.
5. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: The first ceramic sheet and the second ceramic sheet are both made of alumina ceramic sheets.
6. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: When the intermediate with a sandwich structure is heated in vacuum, the heating temperature is 90-95° C. and the heating time is 5-6 hours.
7. The method for preparing a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation according to claim 1, characterized in that: The MXene-OH mixed solution is made of Ti3C2T x The MXene suspension is mixed with potassium hydroxide and stirred.
8. A MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation, characterized in that: The MXene-based electrode material is prepared by the method for preparing MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation as described in claims 1-7.
9. A MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation as claimed in claim 8, characterized in that: The mass specific capacitance of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation is 368.6-625.63Fg -1 .
10. The use of a MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation as claimed in claim 8 or 9, characterized in that: The application of the MXene-based electrode material based on hydrazine hydrate gas expansion-assisted pore formation in supercapacitors.
Citation Information
Cited By
Preparation method and application of high-mechanical-strength porous MXene / PVA composite electrode
CN122025428A